Characterization of vasopressin-responsive collecting duct adenylyl cyclases in the mouse - Strait, Kevin A. (American Physiological Society, 2010)
Little is known about collecting duct adenylyl cyclase (AC) isoforms or regulation in the mouse. We performed RT-PCR for AC isoforms 1–9 in microdissected cortical (CCD) and outer medullary (OMCD) and acutely isolated inner medullary (IMCD) collecting duct. All collecting duct regions contained AC3, AC4, and AC6 mRNA, while CCD and OMCD, but not IMCD, also contained AC5 mRNA. Acutely isolated IMCD expressed AC3, AC4, and AC6 proteins by Western blot analysis. The mIMCD3 cell line expressed AC2, AC3, AC4, AC5, and AC6 mRNA; M-1 CCD cells expressed AC2, 3, 4, and 6, while mpkCCD cell lines contained AC3, AC4, and AC6 mRNA. AVP stimulated cAMP accumulation in acutely isolated mouse IMCD; this was reduced by chelation of extracellular calcium (EGTA) and almost completely abolished by blockade of calmodulin (W-7). Blockade of calmodulin kinase with KN-93 or endoplasmic reticulum calcium ATPase (thapsigargin) also reduced the AVP response. A similar inhibitory effect of W-7, KN-93, and thapsigargin was seen on forskolin-stimulated cAMP content in acutely isolated mouse IMCD. These three agents had the same pattern of blockade of AVP- or forskolin-stimulated AC activity in acutely isolated rat IMCD. AVP responsiveness in primary cultures of mouse IMCD was also reduced by W-7, KN-93, and thapsigargin. Small interfering RNA (siRNA) designed to knock down AC3 or AC6 in primary cultured mouse IMCD significantly reduced AVP-stimulated cAMP accumulation. Together, these data are consistent with a role of AC3 and AC6 in the activation of mouse collecting duct by AVP.